Electrical conductivity of warm dense silica from double-shock experiments - M. Guarguaglini (Nature Portfolio, 2021)
Warm dense silica is a key component in rocky planets’ mantles, but reproducing the relevant conditions in experiments is challenging. Here the authors use a double-shock technique to achieve such conditions and measure the reflectivity in situ, providing insight into the conductivity and its possible impact on dynamo processes in super-Earths’ mantles.